Infection and outcome of COVID-19 affected patients during 1st and 2nd waves in Bangladesh: a hospital based comparative study - Mazumder, M. Maksudul Islam; Hossain, Homayra Tahseen; Chowdhury, Tasmina; Reza, Ishrat Binte; Arafat, Quazi Audry; Ahasan, H. A. M. Nazmul (International Journal of Advances in Medicine, 2023)
Background: COVID-19 emerged as one of the worst pandemics in human history in December 2019. Despite a relatively low infection rate in Bangladesh for seven weeks from mid-January, there were still 287 deaths in February, marking the lowest monthly death toll since May 2020. This study aimed to analyze the infection and outcomes of COVID-19 patients during the first and second waves in Bangladesh. Methods: This cross-sectional observational comparative study conducted at the Popular medical college hospital, 190 COVID patients were enrolled during the first wave (Mid-June to Mid-August 2020), and 179 COVID patients were enrolled during the second wave (Mid-March to Mid-April 21). Result: Mean age was 52.85±15.36 years in the first wave and 55.42±14.20 years in the second wave (p=0.097). Male patients predominated in both waves (p=0.082). Common symptoms, such as fever, cough, and respiratory distress, were similar. The second wave had a higher percentage of patients with diabetes. CRP levels increased in the first wave, while D-dimer levels were higher in the second wave. HRCT reports indicated minimal COVID-19 involvement. Most patients were discharged, with a small percentage referred to higher centers, and the mortality rate was not significant (p=0.600). Conclusions: The study highlights the differences in various factors related to COVID-19 between the first and second waves of COVID-19 in Bangladesh. Although the demographic status was similar in both waves, it provides valuable insights for medical consultations.